Validação de método de manejo para maximizar a produtividade apícola na região do Pampa Gaúcho - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Beekeeping is the sustainable breeding of Apis mellifera for the production of honey, propolis,wax and other products, or for pollination of crops. Due to its diverse floral resources, Brazilis a promising country for this activity, currently being one of the main exporters of honeyproduced by Africanized bees. Rio Grande do Sul is currently the largest honey producerinthe country, reaching 8,000 to 10,000 tons annually. However, the volume of honeyproduction does not indicate high productivity. Proper management of the apiary is oneofthekey factors in obtaining significant quantity and quality of the final product. Therefore, thisstudy aimed to improve the management technique for honey production in the municipalityof São Gabriel – RS. To this end, traditional management techniques and those of beekeeperAldo Machado dos Santos (AM management) from São Gabriel, RS, Brazil were evaluatedand compared. The process included weekly energy feeding (50%sucrose solution), orphannucleus division in summer, necessary wax structure additions, and the introductionofthefirst honey when the colony reached 8 brood structures. The control group receivedfoodonceand all the wax frames at once. The study found that this feeding method doubles honeyproduction, reduces the time needed to introduce the first honey by 1-2 months, minimizescolony loss and reduces varroa infestation in hives. Furthermore, AMmanagement allowsbeekeepers to produce equivalent honey yields in different apiaries, but the absenceoftreatment produces different results. All varroa infestation levels were <5%, peakinginJanuary and July. The results showed that Africanized bee colonies in which AMmanagementwas used had higher honey productivity, shorter time to start production and lower occurrenceof varrose. Therefore, it is a simple, economical and advantageous approach whencomparedto the traditional method
Keywords: Apis mellifera; Técnicas de Manejo; Varroa destructor; Apicultura; Management Techniques; Beekeeping; CNPQ::CIENCIAS BIOLOGICAS